Task Based Learning as an Active Retrieval Approach in the Perception of EFL Students: A Case Study at Bridge Education Manado - Ichiko Wenas; Nihta V. F. Liando; Rinny Rorimpandey (Journal of English Culture, Language, Literature and Education, 2023)
This study set out to find out how participants at The Bridge Education Manado felt about task-based learning (TBL) as a teaching strategy. The poll findings showed that participants generally agreed, highlighting their favorable opinions of TBL's efficiency in fostering student-centered and interesting language learning experiences that promotes a laid-back learning environment where learners' needs and interests are engaged. They acknowledged how language skills were included into TBL, highlighting how well it covered lesson retrieval and made it easier to remember earlier classes and resources as well as to improve language learning experiences and valued their significance and relevance to the actual world. These favorable opinions highlight the usefulness of TBL as a method of instruction that adheres to the fundamentals of communicative language learning and promotes successful language learning outcomes. It is clear from the survey results that TBL is well-liked by students at The Bridge Education Manado. These findings have effects on how the institution teaches languages. First and foremost, it is essential to keep supporting TBL as a pedagogical strategy and to offer ongoing assistance and chances for professional growth to teachers so they can use TBL techniques in the classroom. They would better comprehend TBL ideas, techniques, and material production as a result of this. Collaboration among educators can also encourage the sharing of creative TBL implementation ideas and best practices. Additionally, getting regular input from students can help to enhance TBL practices and better inform instructional design